'Incessant' tachycardias in Wolff-Parkinson-White syndrome. II: Role of atypical cycle length dependency and nodal-his escape beats in initiating reciprocating tachycardias. Issue 9 (September 1976) - Coumel, P; Attuel, P; Slama, R; Curry, P; Krikler, D
Abstract : Descriptions of patients with the Wolff-Parkinson-White (WPW) syndrome and reciprocating tachycardia in whom the initiation of the arrhythmia depended neither on the occurrence of premature beats nor on antecedent cycle-length shortening are given. In 5 the occurrence of escape beats in the bundle of His, usually in the presence of sinoatrial disease, activated the tachycardia circuit, but in the other 2 there were unusual mechanisms related to bradycardia-dependent block in the anomalous pathway, and delayed response to shortening of the atrial cycle length, respectively. Careful assessment of such mechanisms is essential for the correct choice of antiarrhythmic prophylactic therapy.